HUBUNGAN KEBIASAAN KONSUMSI PANGAN, KUALITAS DIET, DAN AKTIVITAS FISIK DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI KOMPLEK TNI AL PASAR MINGGU - Krestina Septriani Prayitno (2023)
Hypertension is a non-communicable disease which is a serious health problem. Based on the 2018 Riskesdas data, the prevalence of hypertension in Indonesia is 34,11%. The prevalence of hypertension has increased with age. The prevalence of hypertension is vulnerable to age 55-64 years, 65-74 years, and 75 years and older, respectively 55,23%, 63,22%, and 69,53%. This study aims to determine the relationship between food consumption habits, diet quality, and physical activity with the incidence of hypertension in the elderly at the Pasar Minggu Navy Complex. This study used a cross sectional design with a sample of 66 respondents taken by purposive sampling technique. Data was collected by measuring blood pressure, the Food Frequency Questionnaire (FFQ), the Healthy Eating Index-2015, and the Baecke questionnaire. Relationship analysis was carried out using the chi-square test. The results of this study showed that there was no relationship between sodium consumption (p = 0,805), fat consumption (p = 0,460), quality of diet (p = 0,497), and physical activity (p = 0,486) with the incidence of hypertension in the elderly at the Pasar Minggu TNI AL Complex. The conclusion of this study is that there is no relationship between sodium consumption, fat consumption, quality of diet, and physical activity with the incidence of hypertension.